SERUM ELECTROLYTE IN CHILDHOOD DIARRHEA AND ITS VARIATION IN SUMMER AND WINTER SEASONS - Iram Naz; Ahmad Omair Virk; Mehboob Alam Siddiqui (Journal of University Medical & Dental College, 2015)
ABSTRACT OBJECTIVE: To determine mean of plasma electrolyte levels in childhood diarrhea and comparison of electrolytes mean levels in winter & summer seasons. STUDY DESIGN: Cross sectional study PLACE AND DURATION OF STUDY: In-patient pediatric medicine department at DHQ hospital Faisalabad from December 2009 to July 2010. MATERIAL AND METHODS: Three hundred and thirty patients suffering from acute gastroenteritis of either sex were enrolled in this study. While those diarrhea patients who were having third degree malnutrition, chronic diarrhea, renal failure or any history of rehydration were excluded from the study. The study was conducted over 8 months duration. Winter season was assigned from December 2009 to March 2010 and summer from April 2010 to July 2010. Blood +samples were collected before starting of any rehydration therapy and serum levels of sodium (Na ) +and potassium (K ) were measured at hospital pathology laboratory. Data were analyzed with SPSS version 10. Percentages for gender were determined more over t-test was applied for evaluating + +seasonal variation of serum levels of Na and K (p-value < 0.05). RESULTS: Plasma electrolytes disturbance occur in patients with acute gastroenteritis. Out of total 330 patients, hypernatremia was seen in 5.45% and 47.87% had hyponatremia. Hypokalemia was documented in 56.36% patients and hyperkalemia in only 0.306%. Hyponatremia and hypokalemia was noted in diarrhea patients in summer season. However, more patients were + + ha ving hypernatremia and hyperkalemia in winter season. The seasonal variations of Na and K levels were found statistically signiﬁcant (p value = 0.000). CONCLUSION: Serum electrolyte levels ﬂuctuate in patients with acute gastroenteritis and seasonal variations in electrolyte changes are observed. Hyponatremia and hypokalemia was documented in summer season while hypernatremia was seen in winter months.